'It's just a Trojan horse for gentrification': austerity and stadium-led regeneration. Issue 1 (2nd January 2018) - Panton, Mark; Walters, Geoff
ABSTRACT: Austerity was the driving principle behind the UK Coalition Government Comprehensive Spending Review in October 2010, with local government facing a disproportionately high share of the spending cuts. Research has focused on the impact of 'austerity urbanism' and urban regeneration; however, there is relatively little focus on sports-led regeneration. This article presents case study research of the stadium-led regeneration project involving Tottenham Hotspur FC and the London Borough of Haringey, focusing on the community perceptions of urban regeneration. It has two aims: first, to understand the local authority's approach to regeneration in the context of the austerity agenda, and second, to understand how this approach was perceived by, and the impact on, those communities living within the geographical locality of the developments. Three themes emerged: first, that austerity led the local authority to adopt a pragmatic approach to regeneration; second, that regeneration in a period of austerity is perceived by local communities as a strategy of gentrification and, third, concerns over the lack of community consultation served as a stimulus for community engagement. Two implications arising from this research are that while community groups in Tottenham had limited success in gaining major changes to the stadium-led regeneration in Tottenham, they have arguably been able to slow down the process. Moreover, they have been successful in bringing together diverse groups across the community to share knowledge in order to challenge further proposals from Haringey Council.